Cocoa Canopy Replacement to Increase Productivity and Plant Resistance to Vascular Streak Dieback - Teguh Iman Santoso; Adi Prawoto; Sudarsianto Sudarsianto (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2013)
Canopy  replacement  with  vascular  streak dieback  (VSD) resistant  clones is  expected  to  reduce  VSD  infestation  by  reducing  space  of  Oncobasidiumtheobromae infection,  and  to  increase  cocoa  yield.  This  experiment  was carried  out  in  endemic  areas  of  VSD  in  Kaliwining  Experimental  Station  of ICCRI  and  Kendenglembu  estate.  Canopy  replacement  technique  in  Kendenglembu  was  done  by  side  cleft  grafting  on  primary  branches  and  top  grafting on  plagiotropic  branches  of  primary  branches.  Number  of  grafted  shoots per  plant,  i.e.  1,  2,  3,  4,  5  and  6  was  used  as  treatments  using  Sca  6  and Sulawesi  1.  The  12  treatments  were  arranged  in  randomized  complate  block design,  each  treatment  replicated  6  times  and  10  plants  per  treatment.  Growth of  shoot,  canopy  coverage  and  development  of  VSD  incidence  were  the  main variables.  In  Kaliwining,  side  cleft  grafting  was  applied  at  1.5  m  above  soilsurface  using  Sulawesi  1  and  Sca  6  clones  as  the  scion  and  TSH  858  and ICS  60  clones  as  rootstocks.  VSD  intensity  was  observed  by  scoring  method. Cocoa  yield  was  the  main  variable.  The  result  showed  that  both  techniques caused  similar  growth  rate  of  the  shoots.  The  rate  of  canopy  covering  by resistant  clones  reduced  VSD  infestation  following  Y  =  -0.7848X  +  69.324 (R²  =  0.995)  equation.  Three  resistant  shoots  per  tree  was  effective  in  reducing  VSD  infestation.  Four  years  after  grafting  were  bean  yield  by  using Sulawesi  1  was  434%  over  control  while  360%  yield  for  Sca  6  compared  to average  control  of  ungrafted  plants  of  ICS  60  and  TSH  858.  Polyphenol content of both resistant clones was higher than that on susceptible ones, however transfer  mechanism  of  that  substance  to  the  susceptible  stocks  is  still  unknown. It  is  concluded  that  canopy  replacement  using  productive  and  resistant  clones is  considered  to  be  an  effective  method  to  overcome  VSD  problem  and  to improve  cocoa  yield. Key words:Theobroma cacao, vascular streak dieback, canopy replacement, yield.